Scopus Indexed Indian Journal of Extension Education: Crafting Improvement Strategy through Altmetric and Bibliometric Analysis (Indian Journal of Extension Education, 2024)
The present paper includes a comprehensive bibliometric and altmetric analysis of the Indian Journal of Extension Education (IJEE), the first and only Scopus-indexed Indian journal from the discipline of Extension Education employing VOSviewer and R-packages. As the official journal of the Indian Society of Extension Education, IJEE covers diverse subject areas, including agricultural extension, rural sociology, information communication technology (ICT) application in agriculture, climate change, and other contemporary social issues. The study examined 543 authors and 263 organizations in co-authorship, considered 625 keywords in co-occurrence, evaluated 156 documents in the citation, and investigated 2849 cited references, 1416 cited sources, and 5203 cited authors in co citation. The results highlighted the influential papers and authors, providing insights into research trends and areas of significance by R-packages. It also explained the thematic map showing the emerging, developing, and already developed research topics in modern trends. The altmetric analysis of the 5 most cited papers from IJEE looked into the research paper’s citations, usage, captures, mentions, and social media penetration. While confirming conventional knowledge, the study identified unique situations indicating the growth of IJEE, contributing valuable perspectives for researchers and stakeholders in extension education and related fields.